Fazeres que tramam territorialidades: uma cartografia de linhas, fios e pontos - Thiago Duarte Flores (2024)
This research cartograph domestic textile activities, producing visibility to the fabric ant territorialities that sew family homes, textile factories and garment workers. By doing this the aim is to go beyond the official histories that cover the importance of these practices and knowledge. The meeting between the researcher and artisans occurs in an engaged manner, weaving dialogue and gesture, participating in manual practices as a form of discourse and knowledge, allowing access to intimate archives. In this way, was possible to do a patchwork of biographies disconnected in time and space, unravel complex relationships, intertwined threads and form new knots. In This weaving, the reverse side of women’s practices revealed the collectivity in apparently solitary work, such as feminist practices that subvert lines of control, as well as processes of territorialization between the lines of these weaves. The research proposes a method of nowledge construction based on joint work, where the researcher’s body is presente, inraveling lines, tensioning stories and weavint non-linear narratives.